Hypoxia Promotes Neutrophil Survival After Acute Myocardial Infarction - Dölling, Maximilian; Eckstein, Markus; Singh, Jeeshan; Schauer, Christine; Schoen, Janina; Shan, Xiaomei; Bozec, Aline; Knopf, Jasmin; Schett, Georg; Muñoz, Luis E.; Herrmann, Martin (Frontiers in Immunology, 2022)
Phagocytosis, degranulation, and neutrophil extracellular traps (NETs) formation build the armory of neutrophils for the first line of defense against invading pathogens. All these processes are modulated by the microenvironment including tonicity, pH and oxygen levels. Here we investigated the neutrophil infiltration in cardiac tissue autopsy samples of patients with acute myocardial infarction (AMI) and compared these with tissues from patients with sepsis, endocarditis, dermal inflammation, abscesses and diseases with prominent neutrophil infiltration. We observed many neutrophils infiltrating the heart muscle after myocardial infarction. Most of these had viable morphology and only few showed signs of nuclear de-condensation, a hallmark of early NET formation. The abundance of NETs was the lowest in acute myocardial infarction when compared to other examined diseases. Since cardiac oxygen supply is abruptly abrogated in acute myocardial infarction, we hypothesized that the resulting tissue hypoxia increased the longevity of the neutrophils. Indeed, the viable cells showed increased nuclear hypoxia inducible factor-1α (HIF-1α) content, and only neutrophils with low HIF-1α started the process of NET formation (chromatin de-condensation and nuclear swelling). Prolonged neutrophil survival, increased oxidative burst and reduced NETs formation were reproduced under low oxygen tensions and by HIF-1α stabilization in vitro. We conclude that nuclear HIF-1α is associated with prolonged neutrophil survival and enhanced oxidative stress in hypoxic areas of AMI.